Systematic Riview: Permainan Ular Tangga tentang Protokol Kesehatan Covid-19 dan Edukasi Kesehatan Anak Sekolah - Enisah Maksum; Murtiningsih Murtiningsih; Iin Inayah (Jurnal Kesehatan Komunitas, 2022)
Coronavirus Disease 2019 (Covid-19) is a pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). Students are able to carry out Evidence-Based Practice, formulate and analyze journals about snakes and ladders and Covid-19 as well as health education. This research method is a systematic review. By searching for journals according to the keyword The Effect of Modified Snakes and Ladders Game on Knowledge Levels of the Covid-19 Health Protocol and Health Education for School Children. Articles are searched through Pro-quest and scholar. The number of articles obtained was 449 articles, after being sorted using a prism, 10 articles were obtained. The modification of the snake and ladder game can provide attachment to players with instructions through educational content about health protocols, player involvement has been tested significantly with the play content variable being the dominant aspect that affects the involvement of children's participants. Snakes and ladders can also be used for other health promotion programs in the health sector, nutrition education using snakes and ladders media materials can produce significant changes in children's knowledge. The promotional media are very interesting and enthusiastic so that the children enjoy their educational process properly. This study is intended to be a reference material for nurses or health workers in developing learning media about snakes and ladders regarding the COVID-19 health protocol.